Pengaruh Disiplin Kerja dan Kompetensi Terhadap Kinerja Pegawai Melalui Motivasi Kerja Sebagai Variabel Intervening pada Sekretariat Daerah Kota Solok - Tiareta, Isra; Yulasmi, Yulasmi; Veri , Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of work discipline and competency on employee performance through work motivation as an intervening variable in the Solok City Regional Secretariat. The type of research used is quantitative. The data analysis techniques used were multiple linear regression analysis and path analysis, by circulating a questionnaire of 98 respondents to the state civil apparatus of the Solok City Regional Secretariat, the questionnaire returned 98 respondents. The results were obtained that there was a positive and significant influence of work discipline on work motivation in Solok City Regional Secretariat Employees. There is a positive and significant influence of competence on work motivation in Solok City Regional Secretariat Employees. There is a positive and significant influence of work discipline on employee performance in the Solok City Regional Secretariat Employees. There is a positive and significant influence of competence on employee performance in Solok City Regional Secretariat Employees. There is a positive and insignificant influence of work motivation on employee performance in Solok City Regional Secretariat Employees. Work motivation does not mediate the influence of work discipline on employee performance in Solok City Regional Secretariat Employees. Work motivation does not mediate the influence of competence on functional positions on employee performance in Solok City Regional Secretariat Employees.